The Influence of Health Education on Breast Self-Examination with Video Media on Knowledge and Attitudes of Female Students at the Institut Kesehatan Immanuel Bandung - Tanti Wili Wiharti; Saurmian Sinaga; Juliyanti Juliyanti (CV Media Inti Teknologi, 2023)
Breast cancer is the most common type of cancer in Indonesia and one of the main causes of cancer mortality, according to GLOBOCON (2020) data. The purpose of this study is to evaluate the knowledge and attitudes of female students at the Immanuel Health Institute in Bandung after receiving BSE health education through video media. Pretest-posttest design with one group is used in this pre-experimental style of study. Utilizing a proportionate stratified random sampling procedure, the sample consists of 68 female students. The Wilcoxon signed rank test was utilized during the analysis process. The results of the study obtained that the majority of respondents' knowledge before being given education was less (39.7%) after being given education, most of them were good (72.1%). The attitude of the respondents before being given the majority of negative education was (54. 4%) after being given the majority of positive education (75.0%). The results of the Wilcoxon statistical test showed knowledge p-value 0.000 (p<0.05) and attitude p-value 0.000 (p<0.05). It can be concluded that there is an effect of providing health education on breast self-examination with video media on the knowledge and attitudes of students at the Institut Kesehatan Immanuel, Bandung. Suggestions for female students to routinely do BSE every month after menstruation.